Ответ: 31 . 108 ; 32 . 1 .
Объяснение:
31 . f(x) =4x³ ; f '(x) = ( 4x³ ) ' = 4 * 3x² = 12x² ; f '(- 3) = 12*( - 3 )²= 12* 9 = 108 .
32 . f(x) = 4√x - 1 ; f '(x) = ( 4√x - 1 ) ' = 4 ( √x )' - ( 1 )' = 4 * 1/2√x - 0 = 2/√x ;
f '(x) = 2/√x ; f '( 4 ) = 2/√4 = 2/2 = 1 .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: 31 . 108 ; 32 . 1 .
Объяснение:
31 . f(x) =4x³ ; f '(x) = ( 4x³ ) ' = 4 * 3x² = 12x² ; f '(- 3) = 12*( - 3 )²= 12* 9 = 108 .
32 . f(x) = 4√x - 1 ; f '(x) = ( 4√x - 1 ) ' = 4 ( √x )' - ( 1 )' = 4 * 1/2√x - 0 = 2/√x ;
f '(x) = 2/√x ; f '( 4 ) = 2/√4 = 2/2 = 1 .